Propagação de campos eletromagnéticos em meios materiais finitos - Lencina, Alberto (2006)
In this thesis, the electromagnetism in material media is considered. It starts from the Macroscopic Maxwell Equations assuming that the fields have a temporal dependence that can be expressed by a Fourier transform. The conservation of the energy, linear momentum and angular momentum are studied from a general point of view. By taking the temporal average of the angular momentum, the orbital and spin contributions were derived without appealing to gauge fields. Following, the central issue is considered: the electromagnetic field propagation in bounded media. It is demonstrated the equivalence in the field propagation from both, ondulatory and energetic, points of view. A plane-parallel-faces medium geometry was considered and the field propagation from the energetic point of view is here established. The resulting set of equations allows to deal with the electromagnetic field propagation in general bounded media. Thus, this equation set, that we called S Formalism, is viewed as a method to solve this kind of problems. This approach emphasizes the possible nonequivalence between the squared field amplitude and the temporal-averaged Poynting vector modulus. This fact motivated the study of such nonequivalence and leaves open the possibility to introduce a new kind of medium, so-called Poynting medium. Since the S-Formalism allows to study media whose response is a function of the temporal-averaged Poynting vector, the light-induced charge carrier media and finally, saturable media are considered